Foreword - Anna-Mart van Wyk; Luc-André Brunet; Eirini Karamouzi (The Thinker)
Africa’s role in nuclear debates and in opposing nuclear weapons is at once consequential and overlooked. Since the 1996 Treaty of Pelindaba, the African continent has been a Nuclear Weapons Free Zone (NWFZ), providing a powerful example of opposition to nuclear weapons on the world stage. More recently, African governments have played leading roles in the implementation of the UN Treaty on the Prohibition of Nuclear Weapons (TPNW), with the aim of worldwide nuclear disarmament. Nuclear debates are becoming more pressing in a number of African countries, as Rosatom, Russia’s state-owned nuclear power company, is building or plans to build new nuclear power plants in Egypt, Burkina Faso, Kenya and Rwanda, amongst others. In South Africa, plans are underway to increase nuclear energy to 2,500 megawatts, while the Koeberg Nuclear Power Station is undergoing refurbishment in order to extend its operating life to 2045.